Implementasi Strategi Lulus Tepat Waktu Sarjana Strata Satu (S1) dalam Era Digital - Kamil, Islamiah; Irawan, Indra Ade; Ratnasari, Anita; Wahyuningsih, Erfiana; Ariani, Meiliyah (Jurnal Pengabdian Kepada Masyarakat, 2024)
Higher education faces new challenges in managing the rapid development of digital technology. One issue that requires attention is the on-time graduation rate of undergraduate students (S1). This research aims to develop and implement effective strategies in increasing the on-time undergraduate graduation rate in the digital era. The community service method is used as an approach in integrating theoretical approaches with practice in the field. This service involves collaboration between Dian Nusantara University, Pancasila University and Prof. University. Dr. Moestopo (Religious), students, and industry to design learning programs that are responsive to student needs in the digital era. The result of this service is the development of technology-based strategies that support online learning, personalized academic mentoring, and the use of data analytics to monitor student academic progress. The evaluation showed a significant increase in the on-time undergraduate graduation rate. The practical implication of this service is the adoption of strategies that have proven effective by other higher education institutions in mitigating the challenges of on-time graduation in the digital era.